2022
DOI: 10.7554/elife.82558
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of reduced cancer risk and tumor suppressor duplications in Xenarthra

Abstract: The risk of developing cancer is correlated with body size and lifespan within species, but there is no correlation between cancer and either body size or lifespan between species indicating that large, long-lived species have evolved enhanced cancer protection mechanisms. Previously we showed that several large bodied Afrotherian lineages evolved reduced intrinsic cancer risk, particularly elephants and their extinct relatives (Proboscideans), coincident with pervasive duplication of tumor suppressor genes (V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(146 reference statements)
0
2
0
1
Order By: Relevance
“…Ainsi, contrairement à la logique du paradoxe de Peto, qui suggère que la résistance au cancer augmente avec la taille ou la longévité de l'animal, l'hypothèse des hyper-tumeurs propose qu'au-delà d'une certaine taille indépendamment, avec de grands corps, une longue durée de vie et un risque intrinsèque réduit de cancer. Les travaux récents de Juan Manuel Vazquez et al (université de Californie, États-Unis) [31] montrent que ce risque réduit de cancer coïncide avec des explosions de duplications de gènes suppresseurs de tumeurs dans les lignées originales de xénarthres 6 et de pilosidés 7 . Chez les paresseux, les cellules se multiplient extrêmement lentement et chez les xénarthres, en général, les cellules ont une susceptibilité accrue aux agents endommageant l'ADN.…”
Section: Le Cas Des Cétacésunclassified
“…Ainsi, contrairement à la logique du paradoxe de Peto, qui suggère que la résistance au cancer augmente avec la taille ou la longévité de l'animal, l'hypothèse des hyper-tumeurs propose qu'au-delà d'une certaine taille indépendamment, avec de grands corps, une longue durée de vie et un risque intrinsèque réduit de cancer. Les travaux récents de Juan Manuel Vazquez et al (université de Californie, États-Unis) [31] montrent que ce risque réduit de cancer coïncide avec des explosions de duplications de gènes suppresseurs de tumeurs dans les lignées originales de xénarthres 6 et de pilosidés 7 . Chez les paresseux, les cellules se multiplient extrêmement lentement et chez les xénarthres, en général, les cellules ont une susceptibilité accrue aux agents endommageant l'ADN.…”
Section: Le Cas Des Cétacésunclassified
“…Using comparative approaches, elephants were found to possess enriched duplication of gene families related to anti-cancer cellular phenotypes, specifically regaining function in a Leukemia-inhibiting pseudogene, and evolving additional copies of tumor suppressor TP53 [ 57 , 58 ]. A follow-up study found that other Xenarthran mammals, including armadillos and sloths, have convergently evolved similar solutions to mitigating cancer risk, suggesting this group should be studied as models for cancer protection [ 59 ].…”
Section: Comparative Genomics Applications For Human Healthmentioning
confidence: 99%
“…Numerous mechanisms have been proposed to explain the evolution of reduced cancer risk, including the gain of additional tumor suppressor genes and the loss of oncogenes. We have previously shown, for example, that duplication of genes with tumor suppressor functions was common in Afrotherians and Xenarthrans, especially in cancer-resistant species such as elephants and armadillos (Vazquez et al, 2022; Vazquez and Lynch, 2021). Here, explore whether gene loss in Afrotheria and Xenarthra is also associated with cancer biology using gene loss data inferred with the Tool to infer Orthologs from Genome Alignments (TOGA) from 17 species (Kirilenko et al, 2023).…”
Section: Introductionmentioning
confidence: 99%